The effects of various concentrations of magnesium stearate on the physical properties of aspirin tablets manufactured by dry granulation - Cayoca, Alexis; Reysag, Carolina; William, Torres D. (Manila Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines, 1996)
The effects of various concentrations of magnesium stearate on the physical properties of aspirin tablets which are manufactured by means of dry granulation were determined using different in vitro tests such as tablet hardness or crushing strength, friability, disintegration, dissolution, and assay. 0.25%, 0.50%, 1.0%, 1.5%, & 2.0% of magnesium stearate were mixed with the granules prior to compression of final tablets. The results show that excess of the lubricant results in (a) decrease in tablet hardness; (b) increase in friability of tablets; (c) increase in disintegration time of tablets; (d) decrease in dissolution rate and consequently of percentage of aspirin released; and (e) decrease in percent assay of aspirin tablets.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, December 1996.
Keywords: Aspirin